WHAT’S THE MATTER WITH THE ASSESSMENT OF THE IMPLEMENTATION OF THE PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) IN TEACHERS? - Rini Kurniawati; Tri Rahayu Budiarti; Yulia Indrawati; Sri Endah Wahyuningsih; Wirastri Setyorini; Lubna Al Jufri; Nita Priyanti; Chandra Apriyansyah (Universitas Panca Sakti Bekasi, 2023)
In efforts to enhance the Pancasila student profile in pupils, teachers play a crucial role. The success of the autonomous curriculum's implementation will be measured by the teacher's capacity to manage the curriculum. The Proyek Penguatan Profil Pelajar Pancasila (P5) implementation of teachers' readiness to use genuine assessments is discussed in this article. The issues faced by kindergarten instructors in the target region 1 IGTKI Duren Sawit, East Jakarta, served as the basis for the research. It was shown that teachers encounter a variety of issues when using authentic assessments, including: (1) the assumption that authentic assessments are too complicated in terms of data collection (2) understanding of the assessment techniques and instruments used in the Pancasila Student Profile Project; (3) there is no training and guidance specifically conducted for making authentic assessment plans. Methods of qualitative research were applied in this study. The study's findings demonstrate that teachers theoretically have a sufficient understanding of authentic evaluations. However, in order to become more proficient and simple to implement, the teacher still needs to learn a lot. Therefore, it might be claimed that the instructor is not prepared to use real assessment. According to the study's findings, instructors' abilities to use diverse techniques for evaluation are enhanced through workshop activities and continued support